2016
DOI: 10.1111/desc.12453
|View full text |Cite
|
Sign up to set email alerts
|

The influences and outcomes of phonological awareness: a study of MA, PA and auditory processing in pre‐readers with a family risk of dyslexia

Abstract: • First paper to report together morphological awareness (MA), phonological awareness and auditory processing in a pre reading sample of high-risk children.• Demonstrates a MA deficit in child with a family risk of dyslexia prior to reading instruction • Findings of a significant difference between controls and children with a family risk of dyslexia in auditory processing skills related to rise-time awareness.• Early pre-reading MA is shown to be a function of PA. AbstractPhonological awareness's direct influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…Studies of pre-reading children have demonstrated that MA is acquired prior to the onset of formal reading instruction (Berko, 1958, Casalis & Louis-Alexandre, 2000Law et al, 2016). However, this early attainment is often limited to aspects of inflectional morphology, such as tense markers '-ed' and the simple derivations which do not involve phonological shifts (e.g.…”
Section: Early Acquisition and Development Of Mamentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of pre-reading children have demonstrated that MA is acquired prior to the onset of formal reading instruction (Berko, 1958, Casalis & Louis-Alexandre, 2000Law et al, 2016). However, this early attainment is often limited to aspects of inflectional morphology, such as tense markers '-ed' and the simple derivations which do not involve phonological shifts (e.g.…”
Section: Early Acquisition and Development Of Mamentioning
confidence: 99%
“…Early MA acquisition has been shown to be dependent on an individual's prereading PA, independent of vocabulary (Carlisle and Nomanbhoy, 1993;Cunningham and Carroll, 2015;Law et al, 2016). Chiat (2001) argued that as children are exposed to speech in context, they segment the target speech stream into available phonological components, which are capable of being generalized or related to the context at hand.…”
Section: Impact Of Phonological Awareness On Early Morphological Awarmentioning
confidence: 99%
See 3 more Smart Citations